A Facile Synthesis of Oxoindenothiazine and Dioxospiro(indene‐2, 4′‐thiazine) Derivatives from (Substituted ethylidene)hydrazinecarbothioamides. (24th June 2014) - Hassan, Alaa A.; Ibrahim, Yusria R.; El‐Sheref, Essmat M.; Ibrahim, Mahmoud A. A.; Bräse, Stefan
<x xml:space="preserve">Abstract</x> (E)‐2‐[2‐(1‐Substituted ethylidene)hydrazinyl]‐5‐oxo‐9b‐hydroxy‐5, 9b‐dihydroindeno[1, 2‐d][1, 3]‐thiazine‐4‐carbonitriles and (E)‐5‐oxo‐[(E)‐(1‐substituted ethylidene)hydrazinyl]‐2, 5‐dihydroindeno[1, 2‐d][1, 3]thiazine‐4‐carbonitriles have been obtained from the reaction of 2‐(substituted ethylidene)hydrazinecarbothioamides with 2‐(1, 3‐dioxo‐2, 3‐dihydro‐1H‐inden‐2‐ylidene)propanedinitrile (1) in ethyl acetate solution. However, (Z)‐6′‐amino‐1, 3‐dioxo‐3′‐substituted‐2′‐[(E)‐(1‐phenylethylidene)hydrazono]‐1, 2′, 3, 3′‐tetrahydrospiro(indene‐2, 4′‐[1, 3]thiazine)‐5′‐carbonitriles were observed during the reaction of N‐substituted‐2‐(1‐phenylethylidene)hydrazinecarbothioamides with (1). The structure assignment of products has been confirmed on the basis of 1H‐, 13C‐NMR, and mass spectrometry, as well as theoretical calculations.